CEGAH ANEMIA SANTRIWATI DI WILAYAH PONDOK PESANTREN KOTA SURABAYA - Mairo, Queen Khoirun Nisa’; Jeniawaty, Sherly; Ginarsih, Yuni; Ngestiningrum, Ayesha Hendriana; Harumi, Ani Media; Alfiah, Siti; Purwanti, Dwi; Sari, Ira Rahayu Tiyar (MAJU : Indonesian Journal of Community Empowerment, 2025)
Anemia remains a global public health problem and continues to pose a significant burden in many developing countries. Several national and regional studies have reported that the prevalence of anemia among adolescent girls ranges from 14% to 50%, depending on location and survey methods, with many studies showing rates exceeding 30% in certain populations. Female students (santriwati) living in Islamic boarding schools (pondok pesantren) are particularly vulnerable to anemia. Common contributing factors include inadequate iron intake, irregular communal eating practices, limited nutritional knowledge, excessive menstrual bleeding, and restricted access to health services. The implementation of the community engagement program consisted of three main stages: (1) Socialization and initial hemoglobin (Hb) screening to obtain a preliminary overview of anemia status; (2) Health education and interactive discussions delivered through lectures, question-and-answer sessions, and educational video presentations; and (3) Evaluation and post-activity monitoring through joint reflections involving both the boarding school administrators and the participants. The combination of Hb screening, interactive counseling sessions, leaflet-based educational media, and institutional support from the boarding schools proved effective in creating a conducive environment for promoting healthy behaviors. However, challenges such as limited availability of Hb testing equipment and negative perceptions toward iron supplementation still need to be addressed through continuous approaches and cross-sectoral collaboration.